Development and validation of the Curricular Elements Evaluation Scale based on the Lifelong Learning Approach in Higher Education - parvin roshanghias; mohamadjavad liaghatdar; bibieshrat zamani; fereydoon sharifian (Shahid Chamran University of Ahvaz, 2021)
Development and Validation of a Lifelong Learning-Based Curriculum Assessment Scale in Higher EducationAbstract Introduction: As one of the important infrastructures of the educational system of any country and the most important source of science and technology production, higher education plays a significant role in the development of lifelong learning. Universities should create a new movement in this direction by conatructing a platform for students to do longlife learning.The present study aims to explain the curricular elements and components of Farhangian University based on the lifelong learning approach and examine the validity of a developed scale in this field.Method: In the present study, exploratory mixed-methods research was used. Initially, qualitative data were collected and analyzed. Then, based on the obtained qualitative results, quantitative instruments were developed. After that, the quantitative data were collected and analyzed to validate the qualitative findings. The statistical population in the qualitative section consisted of experts in the field of lifelong learning, professors of Farhangian University, and curriculum specialists selected via a purposive sampling method. 33 participants were selected and interviewed via the semi-structured interviewing technique to obtain theoretical saturation in the data. In the quantitative section, a descriptive-survey method was employed. The statistical population in this section consisted of professors of the Department of Educational Sciences, Farhangian University of Isfahan Province as 242 individuals, among whom 145 participants were selected based on the Krejcie & Morgan table and via a cluster sampling method. Then, the researcher-made questionnaire was distributed among them. Among the returned questionnaires, 103 ones were quantitatively analyzed.Results: The findings of the qualitative section indicated that the curriculum based on the lifelong learning approach in Farhangian University consists of four main elements of goal (with 19 items), content (with 18 items), teaching-learning methods (with 15 items) and evaluation (with 17 items). In the quantitative section, it was also found that based on the results of the Second Order Confirmatory Factor Analysis (CFA), the elements and related items correctly measure the curriculum model for lifelong learning. Discussion: To sum up, it can be stated that the scale designed in 4 elements and 69 items is valid for evaluating the curricular elements based on the lifelong learning approach at Farhangian University. It can be the basis for making policies and reviewing curriculum at Farhangian University.Keywords: Lifelong Learning, Curriculum, the Lifelong Learning Curriculum Scale, Higher Education, Farhangian University.